Ab initio and first principles theoretical investigations of triplet–triplet fluorescence in trimethylenemethane biradicals. Issue 87 (5th September 2016) - Matsui, Yasunori; Usui, Kosuke; Ikeda, Hiroshi; Irle, Stephan
Abstract : Theoretical studies on triplet–triplet (T1 → T0 ) fluorescence of the arylated trimethylenemethane (TMM) biradicals, 3 2˙˙, were carried out using post-Hartree–Fock ab initio and various first principles density functional theory methods. Abstract : Theoretical studies on triplet–triplet (T1 → T0 ) fluorescence of the arylated trimethylenemethane (TMM) biradicals, 3 2˙˙, were carried out using post-Hartree–Fock ab initio and various first principles density functional theory methods. Analysis of optimized geometries including bond alternations and spin distributions indicates that the triplet ground ( 3 2˙˙ ) and excited ( 3 2˙˙* ) states of these biradicals have aromatic and quinoidal characteristics, respectively. Inspection of their calculated electronic structures shows that, in comparison to 3 2˙˙, one of the spins in 3 2˙˙* is more delocalized onto arene-rings linked to the TMM framework.